2014
DOI: 10.1103/physrevlett.112.047004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Nonequilibrium Distribution of Quasiparticles in the Microwave Response of a Superconducting Aluminum Resonator

Abstract: In a superconductor, absorption of photons with an energy below the superconducting gap leads to redistribution of quasiparticles over energy and thus induces a strong nonequilibrium quasiparticle energy distribution. We have measured the electrodynamic response, quality factor, and resonant frequency of a superconducting aluminium microwave resonator as a function of microwave power and temperature. Below 200 mK, both the quality factor and resonant frequency decrease with increasing microwave power, consiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 39 publications
(46 reference statements)
8
120
2
Order By: Relevance
“…We also find that this optically-induced loss decreases with increasing microwave drive within the range of rf powers and optical intensities that we used in our experiments. The reason for this behavior is similar to the higher temperature case described by de Visser et al 13 . In this regime the rf drive causes a redistribution of the quasiparticles such that f (E) increases for E ≥ ∆ + hf r and decreases for ∆ ≤ E ≤ ∆ + hf r .…”
Section: Loss From Nonequilibrium Distribution Of Quasiparticlessupporting
confidence: 89%
See 4 more Smart Citations
“…We also find that this optically-induced loss decreases with increasing microwave drive within the range of rf powers and optical intensities that we used in our experiments. The reason for this behavior is similar to the higher temperature case described by de Visser et al 13 . In this regime the rf drive causes a redistribution of the quasiparticles such that f (E) increases for E ≥ ∆ + hf r and decreases for ∆ ≤ E ≤ ∆ + hf r .…”
Section: Loss From Nonequilibrium Distribution Of Quasiparticlessupporting
confidence: 89%
“…The phonon escape time τ e = 8.96 ns = 34τ φ was set to maintain power balance for the absorbed optical power for ≈ 15%. This value is about an order of magnitude larger than the equivalent value used by Goldie and Withington 31 and de Visser et al 13 , however it is within the range of reported values for τ e for Al on sapphire 37 . We found that relatively large changes in τ e resulted in relatively small changes in σ 1 and σ 2 .…”
Section: Quality Factor and Frequencysupporting
confidence: 59%
See 3 more Smart Citations